Complete morphometric analysis of jugular foramen and its clinical implications - Das, Sushant Swaroop (J Craniovertebr Junction Spine, 2016)
INTRODUCTION: Tumors affecting structures in the vicinity of jugular foramen such as glomus jugulare require microsurgical approach to access this region. These tumors tend to alter the normal architecture of the jugular foramen by invading it. Therefore, it is not feasible to have correct anatomic visualization of the foramen in the presence of such pathologies. Hence, a comprehensive knowledge of the jugular foramen is needed by all the neurosurgeons while doing surgery in this region. AIM: Due to the inadequate knowledge of the accurate morphology of the jugular foramen in different sexes, the aim of this osteological study was to provide a complete morphometry including gender differences and describe some morphological characteristics of the jugular foramen in an adult Indian population. MATERIALS AND METHODS: The study was done on 114 adult human dry skulls (63 males and 51 females) collected from the osteology museum in the department. Various dimensions of both endo- and exocranial aspect of jugular foramen were measured. Presence and absence of domed bony roof of jugular fossa and compartmentalization of jugular foramen were also noticed. Statistical analysis was done using Chi-square test and Student's t-test in SPSS version 23. RESULTS: All the parameters of right jugular foramen were greater than the left side, except the distance of stylomastoid foramen from lateral margin of jugular foramen (SMJF) which was greater on the left side. Gender differences between various measurements of jugular foramen, presence of dome of jugular fossa, and compartmentalization patterns were reported. CONCLUSION: This study gives knowledge about the various parameters, anatomical variations of jugular foramen in both sexes of an adult Indian population, and its clinical impact on the surgeries of this region.